The concentration of matrix metalloproteinase 9 in the tumor and peritumoral tissue as a prognostic marker in the breast cancer patients - Cvetković, Danijela M.; Milošević, Bojan Z.; Cvetković, Aleksandar M.; Ninković, Srdjan M.; Jovankić, Jovana V.; Jovanovic, Dalibor V.; Marković, Snežana D. (Vojnosanitetski pregled, 2021)
Background/Aim. Breast cancer is one of the most common malignancies among women all over the world. Tumor microenvironment represents one of the main regulators of tumorigenesis. We investigated the role of matrix metalloproteinases 9 (MMP-9) concentration in peritumoral tissue as a prognostic marker in the breast cancer patients. Methods. The ELISA test was used to determine a total MMP-9 concentration in carcinoma and peritumoral tissue sample in the patients with breast cancer. Comparison of MMP-9 protein expression with the clinicopathological parameters was evaluated. Results. Peritumoral tissue at 3 cm distance from the tumor produces more MMP-9 than the tumor itself. The ratio of concentrations of MMP-9 in the tumor and peritumoral tissue considerably changes in favor of peritumoral tissue with the increase of tumor size and the involvement of axillary lymph nodes. In N0 stage, the concentration ratio of MMP-9 in the tumor and peritumoral tissues was 1 : 1.44, but in the N2 stage, the ratio was 1 : 26.5. Conclusion. In patients with breast cancer even in an early stadium there is a change in MMP-9 concentration in peritumoral tissue. We can extract the group of patients at increased risk for the development of lymph node metastasis. A statistically significant difference between the concentrations of MMP-9 in the peritumoral tissue and cancer tissue exists only in case of metastatic disease not in MO stadium implying need for early detection of still unknown metastases in such patients.